The Implementation of a Neuroscience Approach in Improving Islamic Religious Education Learning in Class V at SD Negeri 01 Gading Jaya - Fauzi, Ahmad Ikhwan; Setiawan, Dedi; Irhamudin, Irhamudin (International Journal on Advanced Science, Education, and Religion, 2025)
The development of science and technology, especially in the field of neuroscience, has brought significant changes to the world of education, including Islamic Religious Education (PAI). Neuroscience, as the study of the nervous system and brain, provides valuable insights into the learning process, which can be utilized to improve the effectiveness of PAI learning. This research aims to analyze the implementation of the neuroscience approach in PAI learning in class V of SDN 01 Gading Jaya. The research method used is a qualitative case study with data collection techniques through observation, interviews and documentation. The research results show that neuroscience approaches, such as the use of instrumental music, brain gym, chunking strategies, and brain breaks, can increase students' motivation, understanding, and involvement in PAI learning. However, challenges such as limited time, supporting facilities, and differences in student learning styles are still obstacles. Proposed recommendations include teacher professional development, resource allocation, formation of a community of practitioners, classroom action research, and collaboration with parents. It is hoped that this research can contribute to the development of PAI learning models that are more effective and characteristic in the digital era